Political Communication of New Political Parties: Semiotic Study of The Ummat Party of West Java Province Regional Leadership Council of The Ummat Party of West Java - Sutrisno (Journal of Indonesian Social Sciences and Humanities, 2022)
This research aims to analyze the political communication of the Ummat Party as a new political party in Indonesia, especially in the context of West Java Province. Using a qualitative approach with case studies, this research adopts Charles Sanders Pierce'sSemiotics theory to identify signs, objects and interpretants from the Ummat Party's political communication. The focus is on figures, political machines, and capital (funds and support from mass organizations). The research results show a pattern of political communication that includes these aspects, illustrating the Ummat Party's efforts to build image and support amidst the dynamics of national politics. This research is important for understanding how new political parties such as the Ummat Party influence Indonesian politics and whether they will be a vanguard or a burden in national political communication.